Modelling the household cost of paediatric malaria treatment in a rural county in Kenya: do non-user fee payments matter? A partial cost of illness analysis - Maurice Onditi Kodhiambo; Julius Otieno Oyugi; Beatrice Kagai Amugune (BMJ Open)
Objective The objective of this study was to develop an econometric model for the cost of treatment of paediatric malaria from a patient perspective in a resource scarce rural setting of Homa Bay County, Kenya. We sought to investigate the main contributors as well as the contribution of non-user fee payments to the total household cost of care. Costs were measured from a patient perspective.Design The study was conducted as a health facility based cross sectional survey targeting paediatric patients.Setting The study was conducted in 13 health facilities ranging from level II to level V in Homa Bay County which is in the Eastern shores of Lake Victoria, Kenya. This is a malaria endemic area.Participants We enrolled 254 inpatient children (139 males and 115 females) all of whom participated up to the end of this study.Primary outcome measure The primary outcome measure was the cost of pediatric malaria care borne by the patient. This was measured by asking exiting caregivers to estimate the cost of various items contributing to their total expenditure on care seeking.Results A total of 254 respondents who consented from 13 public government health facilities were interviewed. Age, number of days spent at the health facility, being treated at a level V facility, medical officer prescribing and seeking initial treatment from a retail shop were found significant predictors of cost.Conclusion Higher level health facilities in Homa Bay County, where the more specialised medical workers are stationed, are more costly hence barring the poorest from obtaining quality paediatric malaria care from here. Waiving user fees alone may not be sufficient to guarantee access to care by patients due to unofficial fees and non-user fees expenditures.